(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To conduct an in-depth analysis of inpatient management patterns and clinical characteristics among hypertensive patients admitted to Tam Dao Health Center between 2024 and 2025. Methods: A retrospective cross-sectional descriptive study was performed, encompassing all hospitalization episodes of patients diagnosed with arterial hypertension at Tam Dao Health Center from June 2024 to June 2025. Data were systematically extracted from electronic health records via the eMRHIS platform. Key variables included the total number of pharmacological agents prescribed, duration of hospitalization, presence of comorbid conditions, and utilization of antihypertensive agents across the five principal therapeutic drug classes. Results: A total of 333 inpatient episodes involving hypertensive patients were analyzed. Length of stay ranged from 1 to 17 days, with the majority of admissions lasting between 1 and 8 days. Patients received between 1 and 10 pharmacological agents per hospitalization. The prevalence of comorbidities was 37.2%, with cardiovascular diseases accounting for 16.5% and dyslipidemia 13.8% of cases. The most frequently prescribed antihypertensive classes were calcium channel blockers (73.57%), diuretics (69.37%), and angiotensin-converting enzyme inhibitors (34.83%). Conclusion: This study provides a comprehensive epidemiological and pharmacotherapeutic profile of hypertensive inpatients at a district-level healthcare facility. Findings underscore the clinical complexity of hypertension management in the inpatient setting, highlighting significant rates of polypharmacy and multimorbidity. The results advocate for the implementation of risk-stratified therapeutic approaches and contribute practical evidence to inform guideline-concordant blood pressure management in primary and secondary care settings.